Investment in infrastructure to double the income of small farmers: a successful journey of Gulabrao Patil - Hegde, Narayan G. (Indian Farming, 2018)
Government has to play a critical role in facilitating water resource development, by tapping all the local sources, and if necessary, by bring water from rivers located far away, through lift irrigation schemes. If Government and development banks decide to increase the capacity of Thembu lift irrigation scheme by increasing the operating hours or install additional schemes, additional 6,000 to 8,000 ha of barren lands can be brought under orchards in Atapadi tahashil alone, generating year round jobs at least for 6 to 8 persons/ha. With such schemes in other drought prone areas in the country, an excellent opportunity can be created for millions of marginal farmers to live with dignity and prosperity. Mega-lift irrigation schemes can be given priority for the drought affected parts in Maharashtra, Karnataka, Andhra Pradesh, Rajasthan, and Bundelkhand regions of Madhya Pradesh and Uttar Pradesh.